The feminine rewriting in Wu Shutian’s translation of Song of Songs - Qin, Qian (Journal for the study of the Old Testament, 2025)
Throughout history, numerous female translators have largely remained ‘lost’ due to patriarchal traditions. Within the realm of Chinese biblical translation, Wu Shutian’s version of the Song of Songs has garnered insufficient attention from both translation studies and biblical scholars. This version is characterized by a feminine rewriting approach, evident in aspects of material selection, thematic emphasis, and micro linguistic expression, thus presenting a compelling case for examining the translator’s agency. A closer analysis reveals that Wu Shutian’s translation is profoundly shaped by her identity as a female author and the socio-cultural context of her time. Her feminine rewriting in translating Song of Songs is a fascinating phenomenon deserving more attention in translation studies.